POLITIK HUKUM PENGATURAN PERATURAN DESA DALAM PRODUK HUKUM - Luthfy, Riza Multazam (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
The discussion about Village Regulation arrangements in legal products is closely related to theory of legal politics. Based on a legal politics review, the Village Regulation arrangements in legal products are different. At one time, the Village Regulation was regulated in a Decree of the People's Consultative Assembly (Tap MPR). However, at other times, Village Regulation was regulated in acts (Undang-Undang). The Village Regulation arrangements always changes. There are times when the legal product regarding the formation of legislation regulates Village Regulation in a number of norms. However, there are times when the legal product regarding the formation of legislation does not regulate it. Furthermore, there are differences in Village Regulation arrangements in legal products concerning the formation of statutory regulations. There are legal products that state Village Regulation explicitly in the types and hierarchies of statutory regulations. However, there are also legal products that mention it implicitly through the articles. In addition to it shows that the Village Regulation arrangements in legal products depends on the wishes of the compiler, the position of Village Regulation in the national legal system can also be seen from the regulation in legal products. If the Village Regulation is regulated explicitly through its articles, the position of the Village Regulation will be stronger. If the Village Regulation is regulated implicitly, the position of the Village Regulation is weaker. If acts or other legal products do not regulate Village Regulation, their position is very weak.